Screening for sleep-disordered breathing in people with type 1 diabetes by combining polysomnography with glucose variability assessment. (March 2022) - Basille, Damien; Timmerman, Marine; Basille-Fantinato, Aurélie; Al-Salameh, Abdallah; Fendri, Salha; Lalau, Jean-Daniel
Highlights: Sleep disorders (SDB) were studied in adults with type 1 diabetes. Polysomnography and glucose variability assessment were combined to screen for SDB. SDB was highly prevalent and associated with obesity. Sleep disorders were not associated with glucose variability or low glucose values. Abstract: Aims: There are few published data on sleep-disordered breathing (SDB) in type 1 diabetes (T1DM). Here, we used a combination of polysomnography and glucose variability assessment to screen for SDB. Methods: In a prospective, single-centre study, adults with T1DM underwent polysomnography and continuous glucose monitoring during a single night. We measured high glucose variability and the occurrence of a low or very low glucose level. Mild and moderate-to-severe SDB were defined as an apnoea-hypopnoea index above 5/h and 15/h, respectively. Results: We studied 46 patients (25 men; median age: 42 [35–54]; diabetes duration: 18 years [13–29]; body mass index (BMI): 24.8 kg/m 2 [23.0–28.9]). SDB was present in 17 patients (37.0%) overall (mild SDB: n = 9; moderate-to-severe SDB; n = 8). When compared with the absence of SDB or mild SDB, moderate-to-severe SDB was associated with a higher BMI (29.8 kg/m 2 [27.8–31.1]) and a longer diabetes duration (26 years [18–31]) but not with above-target glucose variability or more sleep disorder symptoms. Conversely, sleep disorder symptoms were not more frequent in patients with above-target glucose variability. Conclusion: SDB was highly prevalent and associated with obesity. According to the methods used here, sleep disorders were not associated with above-target glucose variability or low glucose values.